INTEGRASI ILMU PENGETAHUAN DAN ILMU AGAMA - Nur Azizah Larasati (IAIN Purwokerto, 2020)
The background of this research is related to the efforts to realize the vision and mission of the religious-based school and public education institutions of two junior high schools between Ciania Islamic Cianjur Middle School and Wonosobo Al-Madina Middle School. The purpose of this study is to describe or describe related to the Vision and Mission to be achieved for advancement in a junior high school educational institution that uses the boarding school system, as well as describing the objectives of schools using boarding schools between Al-Madina Wonosobo Middle School and Islamic Middle School Cianjur Scholar. The next one is related to the learning curriculum used. The data collection technique used is documentation. Documents taken from the school via their website. The data that has been collected is then analyzed using a qualitative descriptive analysis model. The results showed that the purpose of the establishment of boarding school-based educational institutions is to carry out a more holistic-comprehensive education, the science of facilities (science and technology) can be achieved goal science (spiritual) can also be balanced and well controlled.